Aplikasi Keamanan Pangan Untuk Meningkatkan Pengetahuan Dan Perilaku Makanan Dalam Pengolahan Makanan Di Rumah Sakit Bolaang Mongondow - Jufri Sineke; Olga Lieke Paruntu; Rudolf Boyke Purba (POLTEKKES KEMENKES MANADO, 2018)
Backround. The organization of food especially in hospitals must be optimal, in accordance with the quality of health service standard and patient disease indication. The cause of misbehavior regarding hygiene and sanitation is due to low knowledge or ignorance of things that food handlers should be aware of in order to obtain healthy food. The purpose of this research is to know the difference of knowledge and behavior of food safety implementation of food handler on food processing before and after intervention in hospital in Bolaang Mongondow Raya. Method.The type of research used is Quasi Eksperimen with pretest and posttest design. The research subjects were taken by total sampling totaling 31 people. The study was conducted from July to September 2017 at Bolaang Mongondow Raya Hospital. The knowledge data was collected using questionnaires and behavior data using the check list form. The statistical test used was T-test, at 95% confidence level and significance limit of p <0,05. Result. The results showed that the average value of knowledge before the intervention was 70.53. Knowledge achievements after the intervention averaged 84.73. The magnitude of the increase in the value of knowledge is 14.2. The average value of the behavior before the intervention is 80.32. The average value after the intervention was 89.68. The magnitude of the increase in the value of behavior is 9.36. Conclusions. There are differences in knowledge of food handlers before and after the intervention. There are differences in the behavior of food handlers before and after the intervention.